Phase State Influence on Photoluminescence of MAPb(BrxI1−x)3 Perovskites towards Optimized Photonics Applications - Huda S. Bawazir; Saif M. H. Qaid; Hamid M. Ghaithan; Khulod K. AlHarbi; Abrar F. Bin Ajaj; Abdullah S. Aldwayyan (Photonics, 2022)
Perovskite halide has many advantages that attracted the attention of researchers in the last years, but many challenges prevent the use of halide perovskites in different applications. One of these challenges is the low thermal stability resulting in phase transitions with temperatures. Here, the photoluminescence (PL) characteristics and related phase transitions of different CH3NH3Pb(BrxI1−x)3 (MA(BrxI1−x)3)3 perovskites structures have been investigated under a wide temperature range. The work that has been conducted demonstrates that under temperature, the exciton behavior of the halide anions, I and Br, has a considerable impact on structural phases and the fluorescence process. The obtained results for the temperature dependence of PL for MAPb(BrxI1−x)3 showed a wide range of emission wavelengths, between 500–800 nm with a decrease in PL intensity with increasing temperature. In addition, the ratio of both bromine and iodine in MAPb(BrxI1−x)3 affects the range of phase transition temperatures, where at x = 0.00, 0.25, and 0.50 the first transition occurs below room temperature (orthorhombic to tetragonal) phase and the other occurs above room temperature (tetragonal to cubic) phase. Furthermore, increasing the proportion of bromine causes all the transitions to occur below room temperature. The presented findings suggest a suitable halide component under a temperature-controlled phase transformation to benefit these materials in photonics devices.